2023
DOI: 10.1002/sej.1483
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading adaptation: How digital transformation promotes organizational resilience

Russell E. Browder,
Sean M. Dwyer,
Hope Koch

Abstract: Research SummaryThis study explores how digital transformation can promote organizational resilience when incumbent firms face crises. We examine the intersection of digital transformation and resilience‐seeking processes through two longitudinal case studies of incumbent firms designated as “essential businesses” during the COVID‐19 pandemic. We analyze 72 crisis adaptations the firms implemented during the crisis to understand how previously underutilized digital capabilities upgraded each firm's ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Recognizing these unique aspects of digital transformation as distinct from other transformations, we conceptualize three common types of changes that digital transformation engenders for incumbents-strategic, organizational, and ecosystem transformation. By strategic transformation, we refer to new ways of creating and capturing value enabled by digital technologies, involving creating new business models and/or strategies, developing new capabilities, and/or upgrading existing capabilities (cf., Browder et al, 2024). Such strategic transformation varies along three underlying dimensions-the focus of transformation (whether the focus of transformation is business models, the broader strategy, or underlying capabilities), the centrality of transformation (whether the changes are core or peripheral to the organization), and the disruptiveness of transformation (whether they enhance or destroy existing assets, knowledge, and relationships).…”
Section: Commonalities and Variationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recognizing these unique aspects of digital transformation as distinct from other transformations, we conceptualize three common types of changes that digital transformation engenders for incumbents-strategic, organizational, and ecosystem transformation. By strategic transformation, we refer to new ways of creating and capturing value enabled by digital technologies, involving creating new business models and/or strategies, developing new capabilities, and/or upgrading existing capabilities (cf., Browder et al, 2024). Such strategic transformation varies along three underlying dimensions-the focus of transformation (whether the focus of transformation is business models, the broader strategy, or underlying capabilities), the centrality of transformation (whether the changes are core or peripheral to the organization), and the disruptiveness of transformation (whether they enhance or destroy existing assets, knowledge, and relationships).…”
Section: Commonalities and Variationsmentioning
confidence: 99%
“…Externally, digital transformation has implications for the firm's ecosystem (i.e., Adner, 2021). Reuter and Floyd (2024), in this special issue, suggested that digital transformation entails an ecosystem challenge, requiring firms to complement their value proposition with partners' offerings. Thus, a key strategic choice is whether firms will choose to compete independently or deepen and/or widen their participation in external ecosystems.…”
Section: Editorial Process and Framingmentioning
confidence: 99%
See 2 more Smart Citations
“…As defined by the Development Research Center of the State Council of PRC, digital transformation refers to the building of closed loop of data collection, transmission, storage, processing and feedback, using new generation of information technology. Many studies have emphasized the positive role of digital transformation in organizational change (Hanelt et al, 2021), knowledge management (De Bem Machado et al, 2022), enterprise performance (Liu et al, 2023a, b), organizational resilience when facing crises (Browder et al, 2024), corporate green innovation (He and Chen, 2024) and other aspects. For sustainable development, Schilling and Seuring (2023) emphasized that digital transformation is now of great significance for cultivating new drivers of sustainability and supply chain transformation.…”
Section: Moderating Effectsmentioning
confidence: 99%